(NiZBRANNYE SO^INENIQ (B/s - (NsALTYKOW(B-(N}EDRIN(B, (NmIHAIL eWGRAFOWI^(B,s; (NtURKOW(B, (Na(B. (Nm(B.,s ((NmOSKWA (B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1989)
(Nw KNIGU IZWESTNOGO RUSSKOGO PISATELQ m(B. (Ne(B. (NsALTYKOWA(B-(N}EDRINA (B(1826 - 1889) (NWO[LI ROMANY (B"(NiSTORIQ ODNOGO GORODA(B", "(NgOSPODA gOLOWLEWY(B" (NI SKAZKI(B.s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NrOS)QÆJSXKA LÆTERATURAs)E -- (NpROZAs -- (NkAZKIs; (NROMANIs; (NL)QÆTERATURNÆ KAZKIs)E